The Effect of Circuit Training on Volleyball Sports Ability in Students - Sahabuddin Sahabuddin; Awaluddin Awaluddin; Davi Sofyan; Arman Fadillah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study is a quantitative descriptive study that aims to determine the effect of circuit training on volleyball games for students at SMAN 3 Pinrang. The method used is a quantitative survey with data collection techniques using agility, strength and endurance tests. The subjects in this study were 30 students of volleyball at SMAN 3 Pinrang. The data analysis technique used quantitative descriptive analysis which was presented in the form of percentages and requirement tests. Based on the results of the study and discussion, the results of circuit training on volleyball sports for students at SMAN 3 Pinrang were agility of 33.33%, strength of 33.33% and endurance of 33.33%. The results of this study can conclude that the effect of circuit training on volleyball games for students at SMAN 3 Pinrang is the same or homogeneous.